2022
DOI: 10.1039/d2cy00574c
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the regulation between crystallinity and oxygen vacancies of BiVO4 affecting the photocatalytic oxygen evolution activity

Abstract: The surface defect structure and material crystallinity determine the catalytic activity and stability of the photocatalyst. In this work, decahedral BiVO4 nanoparticle with uniform size is synthesized by the solution-chemistry...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This means that the reduced ECL intensity might be attributed to the decreased conductivity upon introducing CdAl-LDHs. It is reported that highly crystalline materials with long-range ordered atomic arrangements generally show better electrochemical activity . Therefore, high crystallinity increases the carrier mobility, reduces electron consumption, and improves the subsequent ECL performance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the reduced ECL intensity might be attributed to the decreased conductivity upon introducing CdAl-LDHs. It is reported that highly crystalline materials with long-range ordered atomic arrangements generally show better electrochemical activity . Therefore, high crystallinity increases the carrier mobility, reduces electron consumption, and improves the subsequent ECL performance .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that highly crystalline materials with long-range ordered atomic arrangements generally show better electrochemical activity. 37 Therefore, high crystallinity increases the carrier mobility, reduces electron consumption, and improves the subsequent ECL performance. 38 To verify this hypothesis, the conductivities of CN, CdAl-LDHs, and CN/CdAl-LDHs were investigated by ECSA and EIS measurements.…”
mentioning
confidence: 99%
“…On the contrary, other C 3 N 4 nanoflower samples show relatively poor stability and weak ECL intensity. The great improvement of the ECL stability is probably due to the long-range ordered atomic arrangements in the high-crystalline C 3 N 4 structure, which makes the atoms in the CN framework more stable and inhibits the passivation caused from the overinjected electrons. , …”
Section: Resultsmentioning
confidence: 99%
“…In this work, a nanoflower structure of supramolecular aggregates was employed to reduce the structure defects and increase the crystallinity. 17 The C 3 N 4 nanoflower were successfully prepared through simple thermal polymerization of the supramolecular aggregates (MCA) formed by selfassembly of melamine and cyanuric acid. By adjusting the calcination temperature, we can achieve the purpose of controlling the crystallinity of the C 3 N 4 nanoflower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation